Estudo da ação citotóxica das quinonas sintéticas ENSJ5 e ENSJ1132 em células de câncer de próstata (DU-145) - Mendoza Hernandez, Eleicy Nathaly (2024)
Prostate cancer is the most common malignant neoplasm in the male population, excluding non-melanoma skin cancer, and ranks as the second leading cause of cancerrelated death among men. The diverse and severe side effects associated with chemotherapy drugs have spurred an ongoing quest for the development of new agents to treat prostate cancer and other neoplasms, ones with superior antitumor activity and reduced toxicity. In this context, the exploration of new quinones that exhibit greater selectivity for tumor cells represents a promising avenue in cancer treatment research. The objective of this study was to investigate the in vitro cytotoxic potential and mechanism of action of the synthetic naphthoquinones ENSJ5 and ENSJ1132 against DU-145 tumor cells. These molecules exhibited cytotoxic activity against cells derived from prostate tissue. Flow cytometry analysis revealed a higher proportion of cells treated with ENSJ1132 exhibiting loss of membrane integrity, DNA fragmentation, and mitochondrial depolarization compared to those treated with ENSJ5 and β-lapachone. When a caspase 3 inhibitor was introduced, the viability of cells treated with ENSJ5 increased significantly, suggesting apoptosis induction by this compound. Conversely, in the presence of deferoxamine (DFO), an iron chelator, a more than 4-fold increase in the viability of cells treated with ENSJ1132 was observed, indicating an iron-dependent death mechanism, such as ferroptosis. Furthermore, fluorescence microscopy revealed a significant induction of reactive oxygen species (ROS), superoxides, and lipid peroxidation in cells treated with ENSJ1132, supporting the notion of cell death by ferroptosis. Apparently, the incorporation of two redox centers in ENSJ1132 enhanced its cytotoxic activity compared to ENSJ5, which possesses a single redox center. Collectively, these results suggest that the primary mechanism of action of ENSJ1132 was the induction of ferroptosis, while ENSJ5 induced a similar type of cell death but to a lesser extent. Ferroptosis is characterized by high ROS production, DNA damage, lipid peroxidation, and loss of membrane integrity. Additionally, it was demonstrated that the inhibition of the NQO1 enzyme in DU-145 cells contributes to increased cytotoxicity of both investigated quinones. However, it is not essential, as the compounds maintain their cytotoxic action even against tumor lines lacking NQO1.